2010
DOI: 10.1128/jvi.01134-09
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of Murine Leukemia Virus Gag to the Plasma Membrane Is Mediated by PI(4,5)P 2 /PS and a Polybasic Region in the Matrix

Abstract: Membrane targeting of the human immunodeficiency virus Gag proteins is dependent on phosphatidylinositol-(4,5)-bisphosphate [PI(4,5)P 2 ] located in the plasma membrane. In order to determine if evolutionarily distant retroviral Gag proteins are targeted by a similar mechanism, we generated mutants of the matrix (MA) domain of murine leukemia virus (MuLV) Gag, examined their binding to membrane models in vitro, and analyzed their phenotypes in cell culture. In vitro, we showed that MA bound all the phosphatidy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
97
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(103 citation statements)
references
References 61 publications
4
97
1
Order By: Relevance
“…The MA domain of Gag contains a bipartite signal that promotes stable interaction with the plasma membrane: a N-terminal myristyl group and a patch of basic residues within MA that interacts specifically with PI(4,5)P 2 , a class of phospholipids that resides exclusively in the plasma membrane. [65][66][67] What was less clear until recently is how the viral genome is recruited to assembly sites. Characterization of the localization of two lentiviral genomes in live cells, in the presence or absence of Gag, revealed that Gag is responsible for the recruitment of the genome to the plasma membrane 61,68 ( Fig.…”
Section: Cellular Site(s) Of Initial Recognition Of Rna By Gagmentioning
confidence: 99%
“…The MA domain of Gag contains a bipartite signal that promotes stable interaction with the plasma membrane: a N-terminal myristyl group and a patch of basic residues within MA that interacts specifically with PI(4,5)P 2 , a class of phospholipids that resides exclusively in the plasma membrane. [65][66][67] What was less clear until recently is how the viral genome is recruited to assembly sites. Characterization of the localization of two lentiviral genomes in live cells, in the presence or absence of Gag, revealed that Gag is responsible for the recruitment of the genome to the plasma membrane 61,68 ( Fig.…”
Section: Cellular Site(s) Of Initial Recognition Of Rna By Gagmentioning
confidence: 99%
“…4), indicating that MA is required for Gag recruitment to cell-cell contact sites. Likewise, when MA was deleted and MLV Gag targeted to the plasma membrane using the PH domain of PLC␦ that binds PIP2 (11,21,36), MLV Gag failed to be recruited to sites of cell-cell contact (Fig. 4).…”
mentioning
confidence: 99%
“…In contrast, basic residues in MA are required for Gag membrane binding via their interactions with the phosphinositide PI(4,5)P2. [99][100][101] In addition for HIV-1, these MA basic residues are also a site for gRNA binding. Thus, it was proposed that RNA would serve as a regulator of Gag assembly.…”
mentioning
confidence: 99%